2017
DOI: 10.1080/0886022x.2017.1361838
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin attenuates experimental contrast-induced acute kidney injury: a role for TLR4/MyD88 signaling pathway

Abstract: Different atorvastatin doses have protective effects on contrast-induced acute renal tubular injury in rats, possibly by targeting TLR4, suppressing TLR4 expression, regulating the TLR4/Myd88 signaling pathway, and inhibiting the expression of downstream inflammatory factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…This study proves that, after CT examination, the incidence of CI‐AKI in the control group is 8%, and that in the observation group is 2%. It is suggested that the use of intensive dose of atorvastatin can effectively reduce the incidence of AKI, which is consistent with the research results reported abroad 20–22 23,24 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study proves that, after CT examination, the incidence of CI‐AKI in the control group is 8%, and that in the observation group is 2%. It is suggested that the use of intensive dose of atorvastatin can effectively reduce the incidence of AKI, which is consistent with the research results reported abroad 20–22 23,24 …”
Section: Discussionsupporting
confidence: 89%
“…25,26 CysC is more sensitive and accurate than SCR and BUN, and it can be used as one of the diagnostic criteria for early renal function damage. 22,27,28 eGFR is more accurate, stable, and comprehensive than CysC, SCR, and BUN in the evaluation of renal function, and it is the most commonly used evaluation index of renal function. 29,30 The values of eGFR were significantly decreased in the control group, but were almost no change in the observation group, indicating that the intensive dose of atorvastatin has a certain protective effect on renal function as indicated as the changes of the levels of SCR, CysC, BUN, and eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Renal tissues affected by high osmotic load could make intense focal or diffuse vacuolization of the proximal tubules or overt tubular necrosis appear ( 20 ). Statins attenuate CIN through modulation of inflammation and endothelial function, besides reducing oxidative stress and apoptosis ( 21 - 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, NF-κB is aberrantly activated in CIN, but NF-κB expression is decreased and renal tissue hyalinization, hemorrhagic casts, and necrosis are reduced after infliximab treatment (Saritemur et al, 2015). And TLR4/Myd88/NF-κB is also involved in the protective pathway (Yue et al, 2017). In addition, a study has revealed that overexpression of miR429 inhibits the NF-κB signaling pathway by targeting programmed cell death 4 (PDCD4) to reduce apoptosis and improve cell viability in a CI-AKI cell model (Niu et al, 2021).…”
Section: Contrast-induced (Ci) Akimentioning
confidence: 99%